The Italian Supervisory Court’s professional culture and practices - Daniela Ronco (Oñati Socio-Legal Series)
This article presents a socio-legal reflection on the role of the Italian supervisory judge in shaping the prison moral environment. The Italian supervisory judges ("magistrati di sorveglianza") officially perform two main functions: supervising the enforcement of sentences; and monitoring application of the law in prisons. They should therefore play a key role in terms not only of achieving the rehabilitative ideal, but also of preventing violations of prisoners’ rights. Nevertheless, traditionally they have never fully accomplished their mission of prison supervision, and only in a very few cases do they regularly visit prisons, since they are usually more focused on other (often bureaucratic and formalistic) tasks. Using ethnographic notes collected while acting as an external expert in an Italian Supervisory Court, in this paper I will reflect on how informal norms affect the ordinary practices and the decision-making process, with reference to both of the above-mentioned institutional mandates.